The Influence Of Leadership Style, Motivation, Work Discipline Job Satisfaction And Performance - Mukti Ali; Rachmad Okta (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2022)
This research was conducted to test how much influence leadership style, motivation, and work discipline have on job satisfaction and performance at Mitra Sehat Mandiri Vocational School, Sidoarjo. This study distributed questionnaires to all existing teachers as research respondents totaling 67 people. From the data collected and processed, it was found that leadership style does not affect job satisfaction. Leadership style influences performance. Motivation affects job satisfaction. Motivation affects performance because of value. Work discipline affects job satisfaction. Work discipline affects performance. Job satisfaction affects performance.